Investigating the stability of phenotype, seed components and powdery mildew resistance of the GmMLO edited soybean plants - Bui, Phuong Thao; Phan, Quyen; To, Thi Mai Huong; Do, Tien Phat (Vietnam Journal of Biotechnology, 2024)
Previously, utilizing the CRISPR/Cas9 system, we had successfully induced targeted mutations in the GmMLO genes of the Vietnamese elite soybean cultivar ĐT26 for the first time. The mutant lines carried homozygous mutations of four or three GmMLO genes (including GmMLO02, GmMLO19, GmMLO23 and/or GmMLO20) with no pleiotrophic effects and increased powdery mildew resistance in the T3 generation. In this study, we selected two representative lines and evaluated them in the T4 generation to see if their phenotype and resistance were maintained stably. The analysis results of agronomic and yield parameters under the net-house conditions indicated that there were no undesired data in the two mutant lines in comparison with the wild-type. In addition, the major nutritional compositions of the seeds including the fatty acids, free amino acids and crude protein content of the mutant lines were similar to the control line. Importantly, the response to Erysiphe diffusa challenge of the quadruple mutant line was still maintained at a moderate resistance level (grade 2.5) as compared to the moderate infection level of the wild-type and the triple mutant line (approximately grade 4). These results again demonstrate that inducing targeted mutations of four tested GmMLO genes via the CRISPR/Cas9 system is not accompanied with undesired traits, and the quadruple mutant line is the potential one with increased powdery mildew resistance maintained stably through generations. This soybean mutant line will be valuable material for further breeding programs as well as being able to be propagated for production.